A study on the interests of local community towards Islamic tourism spot: Masjid Kg. Kling, Melaka - Abdul Kadir, Mohamad Farizuan; Mohd. Yaman, Maheran (Kulliyyah of Architecture and Environmental Design, International Islamic University Malaysia, 2017)
This paper discusses the interest of the local community towards Islamic tourism spot, specifically Masjid Kg. Kling, Malacca. Kg. Kling Mosque is an old mosque located in Malacca. The old mosques in Malacca are considered as historical monuments or historical remains that are highly valuable to the development and Islamic civilisation in Malaysia. Malacca today is a relatively fast-growing state and known as a historic state that is rich with cultural diversity. Thus tourism sector plays a big role as a major economy catalyst for Malacca. The aim of this research is to study the interest of local community towards Islamic historical places which would give impact on tourism. In order to achieve the goal, three objectives had been created which are to identify activities that can be conducted in order to revive the zeitgeist of the mosque, to improve the accessibility to the mosque which reflects the design itself that must be user-friendly user to all walks of life including person with disabilities (PWD) and to stimulate the local influx to the mosque that consists of tourists and expatriates as well as to encourage interactions among them. This research has been conducted in five stages: introduction, literature review, data collection, data analysis and conclusion. There are five data collection techniques applied which are: observation with photographs documentation, literature review and survey questionnaire. From the observation and survey conducted, promising results could be seen in the efforts of improving the Islamic tourism sector and strengthening the mutual understanding between the local communities and tourists. It is also hoped to embody the local community’s interest towards Islamic tourism spots which have been established in terms of its implementation in Malaysia; thus leaving a profound impact to this sector. To improve the local interest on Islamic tourism spots, some recommendation were outlined. The selection of the suitable plant materials or planting palette according to the area, functional designs in term of the typology and good preservation for heritage purposes and the space planning should be integrated with the needs of PWD. Overall, this study marks a significant measure on interest of the local community towards Islamic tourism spots in Malacca.